Exploring the diversity of cannabis cannabinoid and non-cannabinoid compounds and their roles in Alzheimer's disease: A review - Hanane Doumar; Hicham El Mostafi; Aboubaker Elhessni; Mohamed Ebn Touhami; Abdelhalem Mesfioui (IBRO Neuroscience Reports)
Cannabis sativa is recognized for its chemical diversity and therapeutic potential, particularly in addressing neurodegenerative diseases such as Alzheimer's disease (AD). Given the complexity of AD, where single-target therapies often prove inadequate, a multi-target approach utilizing cannabis-derived compounds may offer promising alternatives. This review first highlights the chemical diversity of cannabis by categorizing its compounds into cannabinoids and non-cannabinoids. It then examines studies investigating the effects of these compounds on AD-related pathological features. By synthesizing existing knowledge, identifying research gaps, and facilitating comparative analysis, this review aims to advance future research and understanding. It underscores cannabis's potential as a multi-target therapeutic strategy for AD, contributing valuable insights to ongoing scientific discussions.